In vivo study of antimicrobial activity of fermented coconut water with different solvent against sheath brown rot of rice / Fatin Amirah Bakhari - Bakhari, Fatin Amirah (Faculty of Plantation and Agrotechnology, 2018)
Oryza sativa is one of important crops in Malaysia where most of Malaysian consumed rice in daily life. Many countries are concern of to the improvement rice productivity as human population grows up. Such the improvements are on the quality and productivity of rice. Bacterial sheath brown rot disease caused by Pseudomonas fuscovaginae are considered one of new disease and getting widespread in worldwide. Unfortunately, sheath brown rot disease of rice are cause abundant loss of yields almost 100%, and reduce the productivity and quality of rice. Meanwhile, fermented mature coconut water has been reported that have a potential in controlling the disease. However, antimicrobial activity of the fermented mature coconut water extract was not studied yet. Hence, the objective of this study are aim to screening potential of fermented coconut water extracted with different solvent against the rice bacteria pathogen, Pseudomonas fuscovaginae in vivo and to evaluate response of different rice variety that have been treated by fermented coconut water with different solvent against Sheath brown rot of rice. The in vivo experiment was carried out with pre-inoculation approach where the fermented mature coconut water extract were applied to the rice plant, then followed with inoculation of bacteria suspension by inoculating of bacteria suspension pathogen, Pseudomonas fuscovaginae. The length size of lesion appeared was measured in the next day until 7 days. The results obtained from this study, the treatment methanol solvents are showed that least length of lesion as compared the treatment with aqueos solvents. It is indicates that methanol solvents could be a possible as pontential in reducing the growth of Pseudomonas fuscovaginae.